KEPEMIMPINAN DAN SPIRITUALITAS: STUDI KEPEMIMPINAN KH. ABDURRAHMAN WAHID - Firdaus, Rifqi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2023)
Spiritual leadership is leadership that brings worldly matters to the ukhrowi (divine) dimension. who is able to inspire, influence through setting an example, and serve with compassion. One of the nation's leading figures and also a Muslim intellectual, namely KH. Abdurrahman Wahid or Gus Dur. This research is in the nature of a literature study, where the researcher is to obtain the results of an in-depth study related to literature on Spiritual Leadership, Gus Dur's leadership study. His views on various issues are always assessed with Islamic universalism which prioritizes spiritual values. In his leadership he strictly prohibited Islam from using violence because Islam is a peaceful religion. However, he allowed using violence when the situation was urgent. But as long as the path of peace can still be pursued, he forbids using violence, because Islam is a religion that is rahmatan lil alamin. In the political field, for Gus Dur, democracy means equal rights and status of every citizen before the law, regardless of differences in ethnicity, religion, gender and language. Gus Dur's thoughts on religious tolerance not only use products of traditional Islamic thought, but also emphasize the use of methodology (manhaj), legal theory (ushul fiqh), and legal rules (Qawa'id Fiqhiyah) in the framework of making a synthesis to give birth to new ideas as an effort responding to actual changes in society so that conflict between religions can be avoided.